Antiphospholipid syndrome onset with hemolytic anemia and accompanied cardiocerebral events: a case report - Zheng, Jie; Wei, Zhao-Yu; Lin, Shi-Chao; Wang, Yong; Fang, Xin (Frontiers in Pediatrics, 2024)
Antiphospholipid syndrome(APS) is a systemic autoimmune disorder that can manifest as thrombosis in the pediatric population, characterized by persistently positive antiphospholipid antibodies. APS is infrequently observed in children and could represent non-criteria manifestations. Case presentation: A six-year-old Chinese female presented with jaundice and dark urine, leading to a diagnosis of hemolytic anemia. Prednisone therapy initially improved her complexion, but she later developed neurological symptoms. Further laboratory tests showed intravascular hemolysis, coagulation abnormalities, and a positive lupus anticoagulant(LA) test result. Magnetic resonance imaging(MRI) scan revealed abnormal signals in the pons and cerebellar hemispheres, and an occluded part of the basilar artery. She was subsequently diagnosed with autoimmune encephalitis and received IG(immunoglobulin) and high-dose glucocorticoid(GC) treatment, leading to improvement in her clinical symptoms. However, the symptoms of hemolytic anemia worsened after two years. Subsequent laboratory assessments demonstrated the presence of intravascular hemolysis, coagulation abnormalities, and positive tests of anticardiolipin, LA, and anti-beta2 glycoprotein I antibodies. Elevated troponin I and N-terminal pro-brain natriuretic peptide levels, along with electrocardiogram and echocardiogram findings, indicated a myocardial infarction and a thrombus-like mass in the left auricle. Brain MRI showed multifocal infarction and cerebrovascular obstruction. She was diagnosed with APS accompanied by hemolytic anemia, cerebrovascular obstruction, and myocardial infarction. After several weeks of treatment with GC, IG, rituximab, hydroxychloroquine alone with low-molecular-weight heparin sodium, and warfarin, there was a marked improvement in the patient's condition.Pediatricians should be familiar with various presentations of pediatric APS to promptly detect possible aPL-related complications and initiate appropriate management strategies early on.